Pete the cat and the family tree - Dean, Kim, 1969-; Dean, James, 1957- (Pete the cat., 2026)
Pete the Cat is making a family tree. He adds Mom, Dad, and Bob. Who is next? Meet the grooviest members of Pete the Cat's super cool family in this highly decodable Level 2 I Can Read Phonics book designed in conjunction with a phonics expert to help kids learn to read. Includes frontmatter with tips on how to support new readers with each sound in the story. --